(untitled) (Groundings Undergraduate, 2024)
Onomastic evidence offers a unique opportunity for us to understand and reflect upon what we find important enough to notice and lend a name to. This paper studies the street nomenclature of Inverness, a city of key importance throughout Scottish history, to explore what can be inferred about its political, religious and historical past from its street naming patterns and priorities. At its core, this paper surveys the diachronic development of Inverness by looking at maps and town plans from different time periods and qualitatively analyzing the ways in which they represent the fundamental ethos of the city.